Teacher candidates' preparedness to address diverse situations that can threaten pupils’ well-being - Salo, Anne-Elina (Elsevier, 2025)
Amid uncertainty, teacher candidates (TCs) face increasingly complex situations when encountering pupils. However, TCs' perceived preparedness to address pupils' well-being threats remains scarcely mapped. We examined this among Finnish classroom TCs (N = 112) through a questionnaire comprising 15 situations. TCs felt least prepared addressing threat- and crisis-related anxiety and addictions, and most prepared observing peer collaboration difficulties and responding to bullying. Distance teaching weakened perceived preparedness, overall. To enhance the realization of children's right to support and TCs' well-being, we call for adopting an ecosystemic approach to well-being and placing emotional–interactional competencies at the core of teacher education.